2020
DOI: 10.1186/s12876-020-01261-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease in a typical African population: a symptom-based multicenter study

Abstract: Background: The prevalence of gastroesophageal reflux disease (GERD) in Africa is not known but is believed to be increasing because of demographic and epidemiologic transition. The main objectives of this study were to determine the prevalence and risk factors of GERD, and its degree of overlap with dyspepsia and irritable bowel syndrome (IBS) in Nigeria, a typical African population. Methods: This was an observational, cross-sectional and descriptive study of adult Nigerians. Diagnosis of GERD was by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
1
12
1
2
Order By: Relevance
“…Dyspepsia and gastroesophageal reflux disease occur frequently in the population at large and have significant overlapping of symptoms; therefore, knowledge of the underlying clinical cause of these symptoms could help perfect the management of upper gastrointestinal diseases. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Dyspepsia and gastroesophageal reflux disease occur frequently in the population at large and have significant overlapping of symptoms; therefore, knowledge of the underlying clinical cause of these symptoms could help perfect the management of upper gastrointestinal diseases. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence was found to be 14.2% based on GERD symptoms of mainly heartburn and regurgitation lasting days, weeks, monthly and yearly. A recent nationwide population based study reported a prevalence of 7.6% in Nigeria [7] . There are several potential explanations for the differences in reported prevalence rates in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…A Doença do Refluxo Gastroesofágico (DRGE) é um distúrbio de evolução crônica, de alta prevalência em países ocidentais, em que o conteúdo gástrico reflui do estômago para o esôfago e órgãos adjacentes. Esse processo, associado a fatores ambientais, leva à presença de sintomas esofágicos e extra-esofágicos como regurgitação, tosse, odinofagia e pirose, sendo esse o principal sintoma responsável por interferir nas atividades diárias e diminuir a qualidade de vida do paciente (NWOKEDIUKO SC, et al, 2020).…”
Section: Introductionunclassified